Enhancing Procurement Practices: A Proposed Framework for the Indonesian National Police - Suci Ramadhani; Basir Segana; Sutrisno Sutrisno (Lembaga Ketahanan Nasional Republik Indonesia, 2025)
Purpose: The proposed research in this paper aims to develop a conceptual framework to enhance procurement capacity and performance within the Indonesian National Police (POLRI) by establishing the strategic role of non-certified procurement officials as a core focus for analysis, which is expected to strengthen institutional effectiveness, accountability in state resource management, and national resilience. Study Design/Methodology/Approach: The study applies a qualitative exploratory approach with normative and institutional analysis to examine misalignment between regulatory requirements and procurement practices, with particular attention to competency standards, digital transformation, and organisational readiness. Findings: The paper is designed to propose an analytical model rather than report empirical results by positioning procurement capability as a strategic function that can strengthen institutional performance and national resilience. Originality/Value: The paper offers a conceptual contribution by developing an analytical framework that positions procurement governance as a strategic factor in national resilience. The framework is intended to inform subsequent empirical research and policy formulation aimed at strengthening professionalism within law enforcement institutions.